Motion parameter estimation based on the block recursive algorithm with finite word length - LIU, P.-C; CHANG, W.-T; SHEN, W.-Z (IEEE transactions on consumer electronics, 1997)
A three parameter motion model can better describe the motion trajectory of the picture element in a video sequence. Combining the features of the block process and recursive estimation, a block recursive algorithm is proposed to calculate these three motion parameters with compensation for the variety of block positions to get a better stability. To simplify the hardware implementation requirements, the representation accuracy of the displaced frame difference and gradient that are given is analyzed. From this analysis we propose a quantized block recursive algorithm with quantized gradient to reduce the computational complexity. With this simplification the quantized motion estimation algorithm has a sufficient computational speed to meet the requirement of real time application with the least accuracy loss.